Child abuse and fabricated or induced illness in the ENT setting: a systematic review. (30th May 2016) - Rees, P.; Al‐Hussaini, A.; Maguire, S.
Abstract : Background: Child maltreatment is persistently under‐recognised. Given that a third of maltreated children may return with serious or fatal injuries, it is imperative that otolaryngologists who are in frequent contact with children are able to detect maltreatment at first presentation. Objective of review: This review aims to identify ENT injuries, signs or symptoms that are indicative of physical abuse or fabricated or induced illness (child maltreatment). Type of review: Systematic review. Search strategy: An all‐language search, developed in Medline Ovid and consisting of 76 key words, was conducted of published and grey literature across 10 databases from inception to July 2015, for primary observational studies involving children aged <18 years. Evaluation method: Each relevant article underwent two independent reviews with full critical appraisal, applying strict quality standards. Results: Of the 2448 studies identified and screened, 371 underwent full review, resulting in 38 included studies that detailed 122 maltreated children. Pharyngeal perforations ( n = 20) were the most frequent abusive ENT injury, predominantly affecting neonates and infants, presenting with dysphagia, drooling, haemoptysis and surgical emphysema. At least 52% of children with abusive pharyngeal injuries had additional co‐existent injuries. The majority of ear injuries were inflicted to the external ear ( n = 11) and included auricular deformity, abrasions, petechiae, lacerations and burns. Fabricated or induced illness cases presented most commonly with recurrent, unexplained otorrhoea or ENT lesions that failed to heal despite appropriate therapy. Conclusions: All clinicians should be familiar with the signs of child maltreatment. Pharyngeal injuries, or injuries to the external ear, presenting in young children without an explicit history of witnessed injury should prompt a child protection referral for full evaluation. Likewise, children who present with recurrent, or apparently intractable symptoms and signs despite appropriate treatment, should raise the possibility of fabricated or induced illness, and discussion with a child protection specialist is advised. Early recognition of possible child maltreatment and instigation of appropriate safeguarding measures are essential to prevent repetition and escalation of injury. This is of paramount importance to otolaryngologists, who have the potential to identify these children in their practice.